Bubble dynamics of a pressure-driven cavitating flow in a micro-scale channel using a high density pseudo-potential Lattice Boltzmann method. Issue 6 (11th April 2020) - Saritha, Gaddam; Banerjee, Raja
Abstract: A single-component multiphase solver based on Lattice Boltzmann method has been developed and was used to study dynamics of a single cavitating bubble subjected to pressure-driven flow in a two-dimensional channel. Simulations were performed with and without contact to the wall. A pseudopotential model coupled with Peng-Robinson equation of state was implemented to incorporate inter-particle force interaction. The solver was validated by comparing the simulated densities with the theoretical co-existence curves at different temperatures for water. Additionally, the contact angle obtained at various adhesive parameters is also validated at 583 K for water. The dynamics of a single cavitating bubble in a two-dimensional channel subjected to a pressure gradient is studied. Displacement of this bubble at different aspect ratios (5, 10) and Reynolds numbers (1–30) when placed along the channel centerline and at off-center positions were studied. Moreover, bubble growth is computed at various contact angles for different aspect ratios and Reynolds number. Dynamic contact angles and contact lengths during the flow are estimated. As the aspect ratio increases, the bubble appears to be more elongated with lower contact angles.